2006
DOI: 10.1177/0149206306293668
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Human Resources Management: Where Do We Go From Here?

Abstract: The authors identify the key challenges facing strategic human resource management (SHRM) going forward and discuss several new directions in both theThe field of strategic human resources management (SHRM) has enjoyed a remarkable ascendancy during the past two decades, as both an academic literature and focus of management practice. The parallel growth in both the research literature and interest among practicing managers is a notable departure from the more common experience, where managers are either unawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
734
0
56

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,141 publications
(822 citation statements)
references
References 59 publications
(95 reference statements)
32
734
0
56
Order By: Relevance
“…• External social networks: affiliations and association memberships; training sources; labour sources; community • Internal social networks: relationships of trust between employer and employee; mutuality of interests; leadership provided by employer; long-term employee loyalty; a team approach; the employer's approach and empathy resource management (SHRM) (Becker and Huselid 2006). SHRM focuses on organisational performance and the role of human resource management systems in solving business problems.…”
Section: Strategic Human Resource Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…• External social networks: affiliations and association memberships; training sources; labour sources; community • Internal social networks: relationships of trust between employer and employee; mutuality of interests; leadership provided by employer; long-term employee loyalty; a team approach; the employer's approach and empathy resource management (SHRM) (Becker and Huselid 2006). SHRM focuses on organisational performance and the role of human resource management systems in solving business problems.…”
Section: Strategic Human Resource Managementmentioning
confidence: 99%
“…'Strategic' refers to the way advantages are realised and the system of capabilities to generate advantages. Porter's (1996) concept of the 'strategy activity system' is relevant in which actors 'deliberately choose[ing] a different set of activities to deliver a unique mix of value ' (1996: p. 64) and in which there is no one 'best' workforce strategy (Becker and Huselid 2006). For instance, strategies that prioritise human resource stability and low turnover of people will often involve employers focusing on 'employee engagement', where employees feel vigorous, dedicated and absorbed at work (Albrecht et al 2015).…”
Section: Strategic Human Resource Managementmentioning
confidence: 99%
“…A study conducted by Farndale et al (2011) shows that employees who perceive that they have the opportunity to voice their opinions regarding changes and influence decision-making, exhibit high commitment to the organization. Becker & Huselid (2006) linked HR practices with commitment by explaining that they may create bonds with organization. Klein, Molloy, and Brinsfild (2012) showed that HR practices along with climate and culture are key organizational factors that influence commitment.…”
Section: Pos and Organizational Commitmentmentioning
confidence: 99%
“…In fact, these two strategic objectives usually pose a considerable amount of looming pressure on all of its stakeholders which could turn out to be a cause of severe financial distress if they are not managed adequately on time. It is because of the fact that financial gains or losses are closely related with employee's job performance and satisfaction (Becker & Huselid, 2006;Huselid, 1995).…”
Section: Introductionmentioning
confidence: 99%